2016
DOI: 10.5755/j01.ms.22.1.7442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives on UV-activated Urethane Acrylate Polymerization Composite Coatings

Abstract: An increased demand for new and improved coating systems, for environmental & health & safety and performance reasons, have appeared during the recent decades. Currently, there is new interest in preparation of thin UV curable urethane acrylate (UA) composite coatings with short-term properties. Cellulose based additives: nitrocellulose, cellulose acetate butyrate, sucrose benzoate and silica were evaluated to determine their influence on unreacted composite characteristics (viscosity, pigment suspension stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…While these variations do impact mechanical performance, the effect is not particularly pronounced. This observed improvement aligns with previous studies that have reported enhanced mechanical strength in crosslinked acrylate polymers as the degree of crosslinking increases 32 …”
Section: Resultssupporting
confidence: 92%
“…While these variations do impact mechanical performance, the effect is not particularly pronounced. This observed improvement aligns with previous studies that have reported enhanced mechanical strength in crosslinked acrylate polymers as the degree of crosslinking increases 32 …”
Section: Resultssupporting
confidence: 92%
“…Traditional UV formulations do not contain solvents and are relatively viscous compared to solvent-borne formulations. That is because acrylate monomers are relatively weak solvents for the acrylated oligomers resins [4], but for this application solvents in tested concentration had too high decrease in viscosity. Remarkable decrease of solvent concentration could allow to achieve required characteristics, and would improve the coating adhesion, decreasing the shrinkage [7].…”
Section: Resultsmentioning
confidence: 95%
“…This has a positive effect on coating adhesion because UV-induced shrinkage will be reduced. The addition of IP should be checked in pigmented systems, to avoid pigment sedimentation [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome pigment sedimentation in gel polish systems, already small concentrations of silica (1 %.wt) can create thixotropic system and do not affect viscosity significantly [6,7].…”
Section: Introductionmentioning
confidence: 99%